Analysis of Microcontroller-Based Electrical Control System for Internet of Things (IOT)-Based Overcurrent - Ika Febriyanti Br Bangun; Beni Satria; Yoffi Andinata (Journal of Information Technology, computer science and Electrical Engineering, 2024)
An effective electrical control system is essential to prevent damage to electronic devices and maintain the continuity of electrical flow. This research aims to design a microcontroller-based electrical control system with overcurrent monitoring and control features using Internet of Things (IoT) technology. The system uses a current sensor to detect excess current and a microcontroller as a data processor, which can automatically cut off the power supply if an excess current is detected. The data from these current sensors will be transmitted to an IoT platform that allows real-time monitoring via mobile devices or computers. In addition, users can remotely control the electrical system, either to turn on or off the electric current, through a web-based or mobile application. System testing is carried out to verify the functionality of the device in monitoring, controlling, and protecting electrical equipment from overcurrent. The results show that this system can detect overcurrent with high accuracy and provide warnings to users in real-time. The implementation of this system is expected to improve energy efficiency and provide optimal protection for electrical equipment on a household and small industrial scale.